2021
DOI: 10.3390/insects12090761
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of the Adventive Egg Parasitoid of Halyomorpha halys (Stål) (Hemiptera: Pentatomidae) Trissolcus mitsukurii (Ashmead) (Hymenoptera: Scelionidae) in France

Abstract: We report the first detection of Trissolcus mitsukurii in France. More than 1860 sentinel egg masses of Halyomorpha halys (BMSB) were exposed in the field during the 2018–2020 period, and 12 specimens of T. mitsukurii emerged from one egg mass. Their taxonomic identification was confirmed both by morphological and molecular analysis. Trissolcus mitsukurii, similar to T. japonicus, is an egg parasitoid of BMSB in its area of origin in Asia, and both species are considered to be candidates for a classical biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…In Europe, several parasitoids attacking the eggs of H. halys have been reported [23,[27][28][29], with Anastatus bifasciatus (Geoffroy) (Hymenoptera: Eupelmidae) being the most abundant native parasitoid among the few native egg parasitoid species; it is capable of developing on viable H. halys eggs [7,23,[30][31][32]. Thus, it is as a potential candidate for augmentative biological control in Europe [30].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, several parasitoids attacking the eggs of H. halys have been reported [23,[27][28][29], with Anastatus bifasciatus (Geoffroy) (Hymenoptera: Eupelmidae) being the most abundant native parasitoid among the few native egg parasitoid species; it is capable of developing on viable H. halys eggs [7,23,[30][31][32]. Thus, it is as a potential candidate for augmentative biological control in Europe [30].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, higher parasitization of H. halys by T. mitsukurii was detected in naturally-laid eggs compared to sentinel eggs (Zapponi et al 2020). In other two studies, T. mitsukurii exhibited remarkable discovery e ciency of naturally laid eggs on plant tissues, with 27.3 to 46.5 % of parasitised egg masses (Scaccini et al 2020;Bout et al 2021).…”
Section: Discussionmentioning
confidence: 89%
“…Induced plant volatiles act on long-distance range and are easily detected by the egg parasitoids, allowing them to rapidly locate the host that is suitable only for a short period of time (Vet and Dicke 1992;Colazza et al 2004). The ability of T. mitsukurii to exploit oviposition-induced plant volatiles for locating H. halys, although it is investigated here for the rst time, was recently hypothesized following results of open eld surveys in northeast Italy or France (Zapponi et al 2020;Bout et al 2021). For instance, higher parasitization of H. halys by T. mitsukurii was detected in naturally-laid eggs compared to sentinel eggs (Zapponi et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, adventive populations of T. japonicus have been detected in Switzerland and in Italy in 2017 and in 2018, respectively (Sabbatini-Peverieri et al 2018;Stahl et al 2019c;Moraglio et al 2020). Furthermore, also adventive populations of Trissolcus mitsukurii (Ashmead) (Hymenoptera: Scelionidae), another Asian parasitoid of H. halys eggs in Japan (Arakawa and Namura 2002;Kamiyama et al 2022), have been found in Europe, in Italy and in France in 2016 and 2021, respectively (Scaccini et al 2020;Bout et al 2021). This species has been considered as another promising candidate for biological control (Sabbatini-Peverieri et al 2020;Caron et al2021;Giovannini et al 2022).…”
Section: Introductionmentioning
confidence: 99%